Precising of Vehicles Handling Valuation - Chalupa, Milan; Veverka, Josef (Manufacturing Technology Journal, 2017)
The article describes the possibilities of vehicle passability testing by the help of computational simulation. It is used here computing simulation system ADAMS AVT. The simulations can help to find quick answers to basic and additional questions of design change influences in the area of testing vehicle passability. The first part of the article contents description of partial computation simulation models construction which the calculations are associated with. There are mentioned the binding conditions of calculations also. There are mentioned and evaluated the results of performed simulation calculations in the second part of the article. These calculations are performed in order to find out an influence of operation conditions on the vehicle passability. Real operation condition is invasive vehicle speed into a slope in this case. Under investigation are the changes of beaten distance uphill that is the vehicle able to overcome.
Keywords: simulation; computational modeling